2008
DOI: 10.1093/ajcn/87.3.577
|View full text |Cite
|
Sign up to set email alerts
|

Dietary and supplementary betaine: acute effects on plasma betaine and homocysteine concentrations under standard and postmethionine load conditions in healthy male subjects

Abstract: Dietary betaine and supplementary betaine acutely increase plasma betaine, and they and choline attenuate the postmethionine load rise in homocysteine concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
2
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 51 publications
5
50
2
2
Order By: Relevance
“…Betaine supplementation lowers plasma homocysteine levels almost immediately, with maximum results obtained within 4 to 6 weeks. 11,15,17,18 It has been shown that betaine doses of 3 and 6 g decreased plasma homocysteine concentrations within 2 hours in healthy adults. 17 No serious adverse effects were noted in any of the studies; but it is important to note that, in 2 studies, betaine supplementation significantly increased total serum cholesterol and low-density lipoprotein (LDL) cholesterol, which are both independent risk factors for cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Betaine supplementation lowers plasma homocysteine levels almost immediately, with maximum results obtained within 4 to 6 weeks. 11,15,17,18 It has been shown that betaine doses of 3 and 6 g decreased plasma homocysteine concentrations within 2 hours in healthy adults. 17 No serious adverse effects were noted in any of the studies; but it is important to note that, in 2 studies, betaine supplementation significantly increased total serum cholesterol and low-density lipoprotein (LDL) cholesterol, which are both independent risk factors for cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…8 Studies in healthy volunteers show that 6 g/d of betaine lowers plasma homocysteine concentrations by 5% to 20%. [9][10][11][12][13][14][15][16][17][18][19][20] The purpose of this study was to perform a meta-analysis of randomized placebo-controlled trials that used daily betaine supplementation to identify the range in betaine's effects on lowering homocysteine.…”
Section: Introductionmentioning
confidence: 99%
“…Glycine betaine is metabolized in mammals by betaine-homocysteine methyltransferase (BHMT), and the increase following feeding is short-lived [26] even though it is not excreted in the urine [27]; DMSP especially is rapidly metabolized by BHMT and would be expected to have a short biological half-life [19,28]. AsB enters tissues as a glycine betaine analog and is not a substrate for BHMT [19] and has a long half-life [5].…”
Section: Discussionmentioning
confidence: 99%
“…[45][46][47] Some investigators have tried to model the effects of HCU for studying betaine dosing by using a methionine-loading strategy but again, the time course of this kind of analysis is not suitable for detecting possible metabolic adaption induced in long-term betaine therapy. 48 In those studies that have used individuals with HCU, the data has been complicated by the need to continue a methionine-restricted diet which, given its efficacy in lowering total Hcy (tHcy), is highly likely to mask any possible diminution in the ability of betaine to lower tHcy over time. 49,50 One previous study investigated the pharmacokinetics (PK) and pharmacodynamic (PD) characteristics of betaine in six patients (aged 6-17 years) with pyridoxinenonresponsive HCU.…”
Section: Optimal Dosage and Timing Of Betaine Treatment In Hcumentioning
confidence: 99%